Explore the effects of forest travel activities on university students’ stress affection - Chang, Wei-Yin; Wang, Xin; Guo, De-Sheng; Nguyen, Lam-Huu-Phuoc; Tran, Ngoc-Huy; Yang, Shuai-Jie; Lin, Hui-Zhong; Wu, Hsiu-Chen; Huang, Chin-Fei (Frontiers in Psychology, 2024)
This study aims to explore the effects of forest travel activities on university students' stress affection. Forty volunteer university students participated in this study. All participants were asked to complete physiological (Heart Rate Variability) and psychological (Brief Profile of Mood State and State-Trait Anxiety Inventory) tests before and after the travel activities. The results reported that students' heart rates were significantly lower after the forest travel activities than before. All domains of negative mood and anxiety decreased from the pre-test to the post-test. This study found that university students could feel less stressed if they went on forest travel activities.